A novel auxetic honeycomb with enhanced in-plane stiffness and buckling strength. (15th January 2017) - Fu, Ming-Hui; Chen, Yu; Hu, Ling-Ling
Abstract: In the present work, a new design of honeycomb is proposed by embedding the rhombic configuration into the normal re-entrant hexagonal honeycomb (NRHH), in order to enhance the honeycomb's in-plane mechanical properties. Both theoretical analysis and numerical simulations are employed to calculate the in-plane mechanical properties of the new honeycomb under uniaxial compression, including Young's modulus, Poisson's ratio and critical buckling strength. The results show that the new honeycomb can maintain auxetic performance, while both the in-plane Young's modulus and the critical buckling strength are significantly improved compared to the NRHH. Comparisons between the present design and other exiting enhanced periodic topologies are also carried out. With respect to them, the present design features superior performances. For these outstanding properties, this layout may provide a new concept for the optimization and design of auxetic materials.